Gone too soon - Hunter, Scott (Great Britain Myrtle Villa Publishing, 2019)
DCI Moran is called to a burial in a local cemetery. But this is no ordinary interment; the body of a young woman, Michelle LaCroix, a rising star in the music world, is still warm, the grave unmarked. A recording reveals the reason for her suicide. Or does it? Why would a young, successful singer take her own life? To unlock the answer, DCI Moran must steer a course through his darkest investigation yet, as the clues lead to one shocking discovery after another...
111327
Keywords: Police -- England -- Fiction; Women singers -- Fiction; Suicide -- Fiction; Criminal investigation -- Fiction; Chanteuses -- Romans, nouvelles, etc; Suicide -- Romans, nouvelles, etc; England; Detective and mystery fiction; Fiction